Three Bi2W21 Tungstobismuthate Clusters Linked by Acetate‐Stabilized Ln Bridges. Issue 3 (11th October 2018) - Liu, Jiancai; Hu, Hanbin; Jia, Xueying; Zhao, Junwei; Song, Yu‐Fei
Abstract : The evolution of tungstobismuthate chemistry is currently attracting wide interest due to its unique structural feature. Herein, we report for the first time three novel lanthanide (Ln)‐containing tungstobismuthates Na6 Li16 [Pr(H2 O)2 (Ac)Bi2 W21 O72 (OH)]2 · 80H2 O (1 ) and Na9 Li13 [Ln(H2 O)(Ac)Bi2 W21 O72 (OH)]2 · 74H2 O (Ln = Gd III (2 ), Dy III (3 ); HAc = acetic acid) by facile one‐pot self‐assembly method. The1 –3 represent the first type architectures from two peculiar [Bi2 W21 O72 (OH)] 13– fragments and one di‐acetate‐chelating [Pr(H2 O)2 (Ac)]2 4+ or [Ln(H2 O)(Ac)]2 4+ linkage. Most importantly, the [Bi2 W21 O72 (OH)] 13– fragment contains two tri‐vacant [BiW9 O33 ] 9– subunits linked with two internal [WO2 ] 2+ groups and one external [WO2 (OH)] + moiety, which is remarkably different from the previously reported one. Photoluminescence (PL) studies reveal that1 and3 display the typical emission originated from the corresponding Ln III cations whilst the PL decay lifetime of3 stems from the common contribution of Dy III ions and [Bi2 W21 O72 (OH)] 13– fragments accompanied by the possible energy transfer from [Bi2 W21 O72 (OH)] 13– fragments to Dy III centers. Magnetic investigation of3 indicates the potential single‐molecule magnet (SMM) character. This work opens a new avenue for fabrication of Ln‐containing tungstobismuthate materials. Abstract : By employing the one‐pot assembly of simple materials in the LiAc aqueous solution, three di‐acetate stabilizing lanthanide‐inserted tungstobismuthates based on rare [Bi2 W21 O72 (OH)] 13– units and one [Pr(H2 O)2 (Ac)]2 4+ or [Ln(H2 O)(Ac)]2 4+ connector have been attained, in which1 and3 display the typical Ln III luminescent emission whilst3 exhibits the potential single‐molecule magnet property.